Patriarchy Ideology and Workload Inequality within Household (Global Journal of Human-Social Science, 2016)
This paper bases on the fact that Patriarchy as a social system and structure enables men in all the roles to which high status is attributed in any society, is crucial in understanding the dominance of men over women, and therefore being a stepping stone to understand the inequalities therein that lead women to begin negotiating for migration. Specifically this paper shows how the patriarchal system among the Gogo people, in Dodoma region Tanzania, creates gender inequalities in society. It examines how the structure of the patriarchy system that emphasizes the power status of male, authority, control of the male and oppression, domination of the man, suppression, humiliation, sub-ordination and subjugation of the women leads to workload inequalities at the disadvantage of women and children. It does so by examining the structure of patriarchal system as being unveiled through gender roles aspect, of the Gogo people. In this aspect there is manifestation of rule by the father and the supremacy of the husband / father within the family, and therefore to the subordination of his wife and his children. The main argument of this paper is that the patriarchal system perpetuates inequalities out of roles played by men and women within the homestead and farm among the Gogo people that lay a foundation for the Gogo women to negotiate for moving outside their communities.
Keywords: emphasizes the power status; women leads to workload inequalities